2010
DOI: 10.1177/0256090920100305
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Mix Elements Influencing Brand Equity and Brand Choice

Abstract: This study develops and empirically tests a model for determining the determinants and effects of brand equity for the Indian passenger car market. Towards the same, the Brand Equity Creation Model developed by Yoo, Donthu and Lee (2000) was expanded and combined with the Brand Choice Model developed by Erdem, et al (1999). The dimensions of brand equity were thought to affect Overall Brand Equity, which in turn affected the final brand choice made by the consumers. The effect that ten selected marketing activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 43 publications
4
25
0
6
Order By: Relevance
“…Chattopadhyay et al (2010) found that brand price had a positive effect on perceived quality, which means that consumers use high price as an important cue in quality perception, especially for global brands: the higher the price, the higher the quality. However, Korean customers tended to have a favorable attitude toward global SPA brands offering trendy merchandise at a reasonable price (Kim, 2007).…”
Section: Cognitive Focusmentioning
confidence: 98%
See 4 more Smart Citations
“…Chattopadhyay et al (2010) found that brand price had a positive effect on perceived quality, which means that consumers use high price as an important cue in quality perception, especially for global brands: the higher the price, the higher the quality. However, Korean customers tended to have a favorable attitude toward global SPA brands offering trendy merchandise at a reasonable price (Kim, 2007).…”
Section: Cognitive Focusmentioning
confidence: 98%
“…For instance, when products are available in a larger number of stores, consumers can benefit from convenience in their purchasing and services (Yoo et al, 2000;Herrmann et al, 2007). Perceived quality had a positive relationship with store image (Chattopadhyay et al, 2010), suggesting that a good store image was likely to increase positive brand attitude. Kim (2004) also found positive effects of price, store image, and advertising on the perceived quality of SPA brands.…”
Section: Cognitive Focusmentioning
confidence: 99%
See 3 more Smart Citations